Community-Based Ecotourism and Its Impact on the Social and Economic Conditions: A Case Study in Blekok, Situbondo Regency, Indonesia - ARSAD, Sulastri; DARYANTO, Afif Olivian; SARI, Luthfiana Aprilianita; SAPUTRA, Dhira Kurniawan; PRATIWI, Fika Dewi (Journal of Environmental Management and Tourism; Vol 12 No 3 (2021): JEMT Volume XII Issue 3(51) Summer 2021DO - 10.14505//jemt.12.3(51).19, 2021)
This study aims to analyse the impact of the implementation of community-based ecotourism on the social and economic conditions of the people of Kampung Blekok. Primary data were obtained from 79 respondents who were selected by purposive sampling. The research method used a descriptive quantitative method. The data used were the characteristics of the people of Kampung Blekok, data on the social and economic conditions of the people of Kampung Blekok before and after the inauguration of the Kampung Blekok Ecotourism. The results show that the group of low and high income showed the decrease of percentage (11.39 and 8.87%, respectively), otherwise the middle and very high-income group presented an increase percentage (8.85 and 11.39%, consecutively). It means people who gained low and high income are reduced and middle and very high-income group are increased. It can conclude that ecotourism activities could affect the social economic of people in kampung Blekok.